Entrepreneurship training under Perlis Youth and Sport Department (PYSD): A curious case of an effectively ineffective program? - Lamsali, Hendrik; Mad Lazim, Halim; Ariffin, Ahmad Shabudin; Salleh, Mohamed Najib; Ab Hamid, Kamal; Taib, Che Azlan; Hassan, Mohamad Ghozali (2015)
Three months ago, Mr Azizi Mustafa, the Head of Youth Development Division in Perlis Youth and Sport Department (PYSD) was called upon by Mr Karim, his director for an emergency meeting. Judging by his body language, Azizi knew that Mr Karim was unhappy.Something wasn’t quite right, assumed Azizi.Mr Karim then showed him a letter from the Ministry of Youth and Sport in which PYSD was required to submit a special report regarding department’s failure to produce many young entrepreneurs in Perlis As the person in charge of the youth development program, he knew that the ministry was actually referring to their flagship program known as the Entrepreneurship Training Program (ETP).On his desk, there were several claim forms submitted by the facilitators from the previous program.The amount was almost RM 10,000. It is almost similar to the limit of each loan provided by the department to successful applicant. He looked on the wall of his office. Several pictures of successful entrepreneurs coming through their program were hanging there. One of them received Entrepreneur of The Year from Malaysia Prime Minister three years ago. Another one on his right just signing a contract worth RM 2 million to supply IT system for a multinational corporation.However, he knew that the numbers was still not enough.Although numerous efforts have been undertaken via various training programs to promote and educate young Malaysian in Perlis to involve in entrepreneurship, the actual numbers who eventualy becoming an entrepreneur was far from encouraging.Both Mr Azizi and Mr Karim knew the importance of entrepreneurs in driving the nation’s economic growth as well as combating unemployment issues. In fact, numerous efforts have been taken by PYSD via the ETP programs to nurture entrepreneurships at all levels involving all kind of activities such as seminars, training, short courses and conferences. Despite all these, the effectiveness of PYSD entrepreneurship training programs remains debatable.Azizi remember two of his favourite quotes by Peter Drucker: “Entrepreneurship is neither a science nor an art. It is a practice" and “What gets measured gets improved” Azizi realized that he need to act fast.He formed a special team and set a three months timeline to carry out the investigation.